Is there any relationship between multiple Intelligences and the teaching-learning process of english in five year old children at Eugenio Espejo Military high school, school Year 2006-2007 - Iza Espinoza, Luis Alberto (2006)
Nowadays many students from Universities, High Schools, Elementary Schools and even professionals have been frustrated when they tried to learn English for this reason they don t want to listen to anything that relates with English and it is due to the way that their teachers taught them in the first basic grade, their teachers didn t motivate them to learn English or didn t apply the correct methodologies or techniques. One of the most important aspects in teaching children to foreign language is motivation, because they don t know what it is, what it is for, why learn it, so the teacher must find the ways how to teach them. Everybody has the wrong idea that the new teachers must teach the lower grades because they aren t difficult to teach, but if we analyze it we can conclude that if the best teachers or the most experts taught kinder or garden students, they wouldn t hate to learn English like nowadays happens.